(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
This study sought to show how financial analysis indicators affected the assessment of bank performance, taking into account that these indicators are a systematic way to process data that is available in order to gather information for decision-making, assess the past and present performance of institutions, and forecast future results. A field study was then carried out in Iraqi banks that are listed on the Iraqi Stock Exchange. According to the study’s findings, financial analysis indicators are used to assess a bank’s ability to borrow money and settle debt by looking over and evaluating its financial accounts from previous periods. Identifying performance anomalies through financial analysis also helps banks perform better in the future.